Eksplorasi Tumbuhan Obat Berpotensi Imunomodulator Di Kecamatan Leihitu Kabupaten Maluku Tengah - Sarmawaty Kotala; Tri Santi Kurnia (Universitas PGRI Palembang, 2022)
ABSTRACTImmunomodulatory is a drug or a substance that can modulate the activity and function of the immune system. If you take drugs that are immunomodulators, they can improve the work of the immune system in the human body, so that they are not easily attacked by infectious diseases. In general, the use of immunomodulatory drugs is in the form of synthetic or chemical drugs. However, it can cause side effects if used in the long term, such as indigestion, headache, fever, skin rash, constipation, and increase uric acid levels. Therefore, one of the solutions is by applying medicinal plants like was done by people in Leihitu District, Maluku Tengah. However, the existence of the plants has not recorded yet. Therefore, it needs a further action to inform larger people. The method of the research was through exploration by doing some techniques, such as, survey, interview to the chief of the village and people who knowing medical plants, and documentation as well as identification by using some relevant references. The results presents there are 46 plant species and belonging to 27 families, medicinal plants with immunomodulatory potential. Plant parts used as immunomodulatory herbal medicines are roots, stems, leaves, fruits, seeds, rhizomes, and tubers.